2012
DOI: 10.4236/ajps.2012.33038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Pigeonpea (<i>Cajanus cajan</i> (L.) Millsp.) Cultivars and Its Wild Relatives Using Randomly Amplified Polymorphic DNA (RAPD) Markers

Abstract: Genetic diversity among and between 16 cultivars of pigeonpea (Cajanus cajan (L) Millsp.) and its wild relatives (C. albicans and C. lineatus) analysed using RAPD. Twenty two random primers with an average of 71.2% polymorphism produced 151 polymorphic bands. Cluster analysis based on these 151 RAPD markers revealed relatively low level (0.434 -0.714) of genetic diversity among cultivars and high level of diversity between cultivars and wild relatives. C. albicans and C. lineatus showed only 0.231 similarity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…Our results also revealed an average of 8.54 loci per primer (Table 3). A close average was also obtained with other legume crops such as pigeon pea using RAPD markers (Yadav et al, 2012). In addition, the maximum percentage of polymorphic markers was 71.4 (BC-298; Figure 1) and the minimum was 50.0 (OPA-05, -09, and -16).…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results also revealed an average of 8.54 loci per primer (Table 3). A close average was also obtained with other legume crops such as pigeon pea using RAPD markers (Yadav et al, 2012). In addition, the maximum percentage of polymorphic markers was 71.4 (BC-298; Figure 1) and the minimum was 50.0 (OPA-05, -09, and -16).…”
Section: Resultsmentioning
confidence: 67%
“…However, only VF-22, VF-23, and VF-24 landraces, which were collected from the Bethlehem region were clustered together. Indeed, the similar agro-climate that characterizes the region may be the reason for showing more similarity with each other and therefore clustering together (Yadav et al, 2012). In addition, landraces of big seed sizes were also grouped together, which also implies high genetic similarities between them, and may belong to the same genotype.…”
Section: Number/frequency Description 37mentioning
confidence: 96%
“…The highest GDs values were found between D. Stratiotes (Ac08) and D. anosnum (Ac14) with 0.90 GDs value then followed by pairwise differences of D. Stratiotes (Ac08) and Dendrobium sp3 with 0.77 GDs value and the smallest GDs value were found between D. Lineale type1 (2) and Dendrobium sp1 (Ac03) with 0.10 GDs value. The calculation results of genetic variation among orchid species in this investigation resemble those of Cajanus cajan, Cajanus albicans, and Cajanus liniatus which have a wide range of genetic differences based on RAPD markers [29].…”
Section: Genetic Variationsmentioning
confidence: 99%
“…Discovery of molecular markers led to genetic diversity analysis using restriction fragment length polymorphism (Sivaramakrishnan et al, 2002), amplified fragment length polymorphism (Panguluri et al, 2006), random amplification of polymorphic DNA (Yadav et al, 2012), microsatellite markers and DArT (Yang et al, 2006). Nevertheless, the molecular basis of most agronomic traits in pigeonpea remains unexplored due to the low level of DNA polymorphism and limited number of validated molecular markers.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 1804-1814mentioning
confidence: 99%
“…Genetic diversity is essential prerequisite in breeding for drought tolerance, increased yields, wider adaptation and desirable quality. Earlier studies on genetic diversity with limited number of genotypes has been reported in pigeonpea viz., 36 elite cultivated genotypes , 45 genotypes (Datta et al, 2013), 16 cultivars and 2 wild relatives (Yadav et al, 2012), 15 genotypes (Shende and Raut, 2013), 49 genotypes (Rekha et al, 2011), 88 accessions (Songok et al, 2010), 16 genotypes (Singh et al, 2008) and 14 genotypes (Chakraborty et al, 2013). These studies however, focused on studying overall genetic diversity among pigeonpea germplasm using genic and genomic SSRs not specifically SSR markers related to drought tolerance.…”
Section: Issn: 2319-7706 Volume 6 Number 4 (2017) Pp 1804-1814mentioning
confidence: 99%